An analysis framework for quantitative evaluation of parametric uncertainty in a cooperated energy storage system with multiple energy carriers. (1st July 2021) - Wang, Jing; Kang, Lixia; Huang, Xiankun; Liu, Yongzhong
Abstract: In order to increase the penetration of renewable energy into process industries, it is essential to develop an energy storage system for effectively coordinating the intermittent supplies of renewable energy and the fluctuating demands, but parametric uncertainty reigns. In this work, a four-step analysis framework to quantitatively evaluate impacts of parametric uncertainty on a cooperated energy storage system with multiple energy carriers was proposed. It features the quantitative uncertainty analysis associated with global sensitivity analysis based on the deterministic optimization model for the system. The implementation of the quantitative uncertainty analysis was demonstrated by a cooperated energy storage system to bridge the intermittent renewable energy and the fluctuating demands in refineries. The critical parameters and their impacts on the total annual cost of the system were analyzed. Results show that the proposed analysis framework and the developed solution strategy are effective in quantitatively evaluating parametric uncertainty of the system. The critical parameters vary dramatically under different penetration ratios of renewable energy, but the hydrogen demand is the dominant parameter in all cases. The proposed approach provides a useful tool to support quantitative analysis of uncertainties for utilization of renewable energy in process industries. Highlights: An analysis framework to evaluate uncertainty in energy storage systems is proposed. Uncertainty analysis combines global sensitivity analysis with deterministic models. A cooperated energy storage system with multiple energy carriers is investigated. The critical uncertain parameters vary with penetration ratios of renewable energy. The framework is useful to quantify uncertainty in design of energy storage systems.